ELEMENTAR GEOMETRIYADA EKSTREMALLİQ MÁSELELER - Tanirbergenov, S.A.; Jalgasova, N.B.; Narekeeva, A.B. (SCIENCE and SOCIETY, 2022)
This article are considered geometrical problems applying the maximum and minimum and their method of teaching for students. There is a set of practical problems and their solutions.